Exploring C-Reactive Protein Levels in Menstruating Female Students: A Descriptive Study - Agiesa Khoirunzia; Herlinda Djohan; Linda Triana; Etiek Nurhayati (MEDICA (International Medical Scientific Journal), 2025)
During menstruation, prostaglandins induce uterine contractions, which contribute to the thickening of the endometrial mucosa and the constriction of blood vessels. Elevated levels of prostaglandins may influence C-Reactive Protein (CRP) levels, a marker that increases in response to inflammation or infection as part of the body's immune response. This study aimed to examine CRP levels in female students during menstruation. A descriptive research design was employed to assess CRP levels in menstruating female students. The sample consisted of blood serum collected from 30 students at Madrasah Aliyah Pondok Pesantren Pembangunan Ushuluddin in Singkawang City. The results showed that among the participants, 5 students aged 16 and 1 student aged 15 exhibited positive CRP levels. Regarding the duration of menstruation, positive CRP levels were detected in 4 students on the first day, 1 student on the second day, and 1 student on the third day. Overall, 20% of the students showed positive CRP levels, while 80% had negative CRP levels. The conclusion indicates that a subset of menstruating female students exhibited elevated CRP levels, particularly during the early days of menstruation. This suggests that menstruation, likely through prostaglandin-induced inflammation, may be associated with an increase in CRP levels in some individuals.